MANAJEMEN STRATEGI PENDIDIKAN DALAM MENINGKATKAN KUALITAS GURU DI SD NEGERI 1 BUMI ARJO KECAMATAN LEMPUING KABUPATEN OKI - Yuliana, Yuliana; Harapan, Edi; Eddy, Syaiful (Jurnal Manajemen Pendidikan, 2024)
This study aims to analyze and describe the planning of strategies to improve the quality of teachers of SD Negeri 1 Bumiarjo, analyze and describe the implementation of strategies to improve the quality of teachers of SD Negeri 1 Bumiarjo, analyze and describe the organization of strategies to improve the quality of teachers of SD Negeri 1 Bumiarjo, analyze and describe the obstacles faced in improving the quality of teachers of SD Negeri 1 Bumiarjo. This type of research is descriptive qualitative using SWOT analysis. Data collection techniques were interviews, observation, and documentation. The data sources were supervisors, principals, and teachers. Data analysis techniques are data reduction, data presentation and data verification. The results of this study show that: 1) The planning of educational strategies to improve teacher quality at SD Negeri 1 Bumiarjo has been well implemented; 2) Implementation of strategies to improve the quality of teachers at SD Negeri 1 Bumi Arjo has been implemented well; 3) The organization of strategies to improve the quality of teachers at SD Negeri 1 Bumi Arjo has been carried out well; 4) The obstacles faced in improving the quality of teachers at SD Negeri 1 Bumiarjo can be overcome well. The results of the SWOT analysis show that there are internal factors that are the strengths and weaknesses of the strategic planning of education to improve the quality of teachers at SD Negeri 1 Bumiarjo.